SETTLEMENT OF DISPUTES OVER DOMAIN NAMES OWNERSHIP AND CYBERSQUATTING IN INDONESIA AND SINGAPORE - Nur Hakiki; Sanusi Sanusi (Student Journal of International Law, 2023)
The article was conducted based on the rise of cybersquatting against domain names in Indonesia, while  the legal protection against cybersquatting of domain names remained ineffective compared to other Southeast Asian countries such as Sungapore. Singapore can be the best country for Indonesia to compare with, due to its already has a perfect legal system and law enforcement toward domain dispute cases. The litigation settlement of domain names in Indonesia emphasizes on the registration aspect to make the court proceeding procedure easier. Meanwhile, in the non-litigation process, Domain Name Dispute Settlement Secretariat (PPND) already set up a new regulation called PPND Policy to settle the domain dispute based on universal standard. In Singapore the settlement of cybersquatting both litigation and non litigation has adopted the universal standard as  stated in Uniform Domain Name Dispute Resolution Policy (UDPR) which empasizes on three elements of cybersquatting evidentiary process.